A Wideband High-Gain Dual-Polarized Slot Array Patch Antenna for WiMAX Applications in 5.8 GHz - Amir Reza Dastkhosh; Hamid Reza Dalili Oskouei (International Journal of Antennas and Propagation)
A low-cost, easy-to-fabricate, wideband and high-gain dual-polarized array antenna employing an innovative microstrip slot patch antenna element is designed and fabricated. The design parameters of the antenna are optimized using commercial softwares (Microwave Office and Zeland IE3D) to get the suitable 𝑆-parameters and radiation patterns. Finally, the simulation results are compared to the experimental ones and a good agreement is demonstrated. The antenna has an approximately bandwidth of 14% (5.15–5.9 GHz) which covers Worldwide Interoperability Microwave Access (WiMAX)/5.8. It also has the peak gain of 26 dBi for both polarizations and high isolation between two ports over a wide bandwidth.